IN UZBEKISTAN RUSSIAN OF THE LANGUAGE IMPORTANCE - Kristina Ivanova Konstantinova; Yusupov Bekzod (Лучшие интеллектуальные исследования, 2024)
Annotation: This article talks about the place of the Russian language in our country, that the Russian language is one of the leading languages ​​of the world, that the language is the most important means of communication between people, that the Russian language is the national language of the Russian people .